Comparison of Biochemical Recurrence–Free Survival Between Periprostatic and Pelvic Lymph Node Metastases of Prostate Cancer. (August 2013) - González-Roibón, Nilda; Han, Jeong S.; Lee, Stephen; Feng, Zhaoyong; Arslankoz, Sehbal; Smith, Nathaniel; Pierorazio, Philip M.; Humphreys, Elizabeth; Deweese, Theodore L.; Partin, Alan W.; Bivalacqua, Trinity J.; Han, Misop; et al.
Objective . To assess the pathologic characteristics and prognostic significance of periprostatic lymph node (LN) metastasis of prostate cancer. The latter was performed by comparing biochemical recurrence (BCR)–free survival in cases of periprostatic LN metastasis versus matched patients showing pelvic LN metastasis. Methods and Materials . We identified 15 patients who underwent radical prostatectomy in our institution (1984-2011) showing positive periprostatic and negative pelvic LN with available follow-up information (group 1). These patients were matched 1:2 to patients with positive pelvic LN (group 2) for pertinent clinicopathologic parameters. Results . Main locations of positive periprostatic LN were posterior base and mid posterolateral. Overall higher rate of positive margins, smaller LN, and metastasis size were encountered in group 1 compared with group 2. At 5 years postprostatectomy, 69% of patients in group 1 were free of BCR, whereas 26% of those in group 2 remained BCR free, suggesting that patients with periprostatic node metastasis appeared to have a lower risk of BCR. However, the difference was not statistically significant ( P = .072). The same was true when adjusted for the effect of prostate-specific antigen, surgical margin status, size of LNs, size of metastasis, age, and year of surgery. Conclusion . Patients with periprostatic node metastasis may have a lower risk of BCR compared with those with metastasis to pelvic LN. Future analysis of larger cohorts will help establish the biologic significance of prostate cancer metastasis to periprostatic LN.